2017
DOI: 10.1016/j.pmrj.2017.08.404
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Gonadal Function and Cardiometabolic Risk in Young Men With Chronic Spinal Cord Injury

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
(70 reference statements)
0
13
3
Order By: Relevance
“…Our findings suggest that the addition of RT to low-dose TRT may be beneficial in inducing muscle hypertrophy of the trained thigh muscles and adjacent glutei muscles. Higher serum testosterone in men with SCI is linked to positive body composition [18] and cardiometabolic outcomes [29]. However, low-dose TRT administered in the current study was not enough to induce trunk, glutei or lower leg muscle hypertrophy.…”
Section: Clinical Relevance Of Hypertrophy Of the Glutei Musclescontrasting
confidence: 56%
“…Our findings suggest that the addition of RT to low-dose TRT may be beneficial in inducing muscle hypertrophy of the trained thigh muscles and adjacent glutei muscles. Higher serum testosterone in men with SCI is linked to positive body composition [18] and cardiometabolic outcomes [29]. However, low-dose TRT administered in the current study was not enough to induce trunk, glutei or lower leg muscle hypertrophy.…”
Section: Clinical Relevance Of Hypertrophy Of the Glutei Musclescontrasting
confidence: 56%
“…The authors showed that persons with lower BMI have serum T level greater than 300ng/dL compared to those with BMI > 25.26 kg/m 2 [12]. In contrast, a recent study showed that BMI was not an influential factor in determining the serum T level in persons with SCI, whereas total body % fat mass was an accurate determinant of circulating serum T level [13]. In the current study, persons with normal T-level (>555 ng/dl) had an average BMI of 21.5 kg/m 2 ; which was significantly lower than those with low-T level (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the association between serum T levels and body composition [13] as well as biomarkers of cardiometabolic health [12,13] in men with SCI and able-bodied men [14]. However, regional body composition assessments were not captured to examine the association of serum T levels with total and regional lean mass, thigh skeletal muscle cross-sectional area (CSA), intramuscular fat (IMF) and VAT [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…62 In young men with chronic spinal cord injury and an accelerated aging process after injury, hypogonadism is linked to an adverse cardiometabolic measure. 63 Therefore, high-quality randomized controlled studies are required to investigate the efficacy and safety of TRT in this population with an increased risk of cardiometabolic diseases. 64 Long-term T therapy reduces the risk of CVD with improvement in cardiometabolic function in men with hypogonadism.…”
Section: Androgens In Cmsmentioning
confidence: 99%